(3HQfGeL bGFe Ydi GdPcGAGJ GdeJYOOI h CKQg ai JfejI egGQGJ GdJacjQ GdEHOGYi h GdJacjQ GdfGbO ddWdHI GdeJahbjf HGdeQMdI GdCSGSjI GdeJhSWI ai adSWjf (B= s A program Based on multiple intelligences and its impact on acreative thinking skills and the critical thinking of excelling students in the preparatory stage in Palestine - (3eQGO YeQ eMeO UGdMs; (3NGdO YHOGdQGRb GdfLGQ (B: s; (3SejQI CHhGdMSf YHOGdSdGe (B: s ((3GdbGgQI (B: s (3eQGO YeQ eMeO UGdM (B: s, 2015)
(3HQfGeL bGFe Ydi GdPcGAGJ GdeJYOOI hCKQg aj JfejI egGQGJ GdJacjQ GdEHOGYj hGdJacjQ GdfGbO ddWdHI GdeJahbjf HGdeQMdI GdCSGSjI GdeJhSWI aj adSWjf (B. (3gOaJ GdOQGSI Edi JfejI egGQGJ GdJacjQ GdEHOGYj hegGQGJ GdJacjQ GdfGbO ddWdHI GdeJahbjf HGdeQMdI GdCSGSjI GdeJhSWI HGSJNOGe HQfGeL bGFe Ydi GdPcGAGJ GdeJYOOI hGdJMbb ef aGYdjJg (B. (3h Pdc Ydi YjfI bhGegG (B(30) (3WGdH ef GdWdHI GdeJahbjf HGdeQMdI GdCSGSjI GdeJhSWI ai adSWjf h Je JbSjege Edi eLehYJjf JLQjHjI h VGHWI eY ELQGA GdJLGfS HjfgeG ef MjK GdYeQ GdRefi h GdJMUjd h GdPcGA h GdJacjQ GdEHOGYi h GdfGbO (B: (3h GSJNOeJ GdOQGSI ebjGSkG ddJacjQ GdGHOGYi h ebjGSkG ddJacjQ GdfGbO h HQfGeLkG dJfejI egGQGJ GdJacjQ GdEHOGYi h GdfGbO dOjge(B: (3h JhUdJ fJGFL EdOQGSI Edi aGYdjI GdHQfGeL GdeSJNOe ai JfejI gPg GdegGQGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe GdJQHjI GdNGUIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJacjQ GdEHOGYis; (3GdJacjQ GdfGbOs; (3GdPcGAGJ GdeJYOOIs